(3GdOhQ GdQbGHi dYedjGJ MaX GdSdGe GdOhdjI Ydi JfajP bhGYO GdbGfhf GdOhdi GdEfSGfi(B. / s - (3eMeO YHO GdMejO GdSjO aQL s; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3YbH EfOdGY GdMQH GdYGdejI GdKGfjI, hGdJi NqdaJ QUjOkG VNekG ef GdVMGjG hGdEfJgGcGJ hGdLQGFe VO GdEfSGfjI, Je EfTGA efXeI GdCee GdeJMOI, MjK JVef ejKGbgG QZHI GdOhd aj GdSYi fMh GdSdGe hGdJfejI hGdJYGhf ef CLd EYGOI GdESJbQGQ hGdCef GdOhdjjf(B. (3hJdLC efXeI GdCee GdeJMOI dGSJNOGe YOOkG ef GdCOhGJ ddeSGYOI ai EjL`GO MdhdkG SdejI ddUQGYGJ GdOhdjI, eKd GdOHdheGSjI GdhbGFjI, hUfY GdSdGe, hEfTGA YedjGJ MaX GdSdGe GdJj Jbhe Ydi fTQ CaQGO ef GdYScQjjf ef GdOhd GdeTGQcI Hjf CWQGa GdfRGY GdeSdM HGdEVGaI Edi GdeTGQcI ai LghO HfGA GdbOQGJ ddeDSSGJ GdhWfjI ddOhd GdeVjaI ddYedjI ef NdGd Gdechfjf GdTQWi hGdeOfi, JYed LejYgG JMJ dhGA GdefXeI GdOhdjI(B. (3ceG Je EHQGe EJaGbjGJ Lfja YGe (B(1949) (3hHhJhchdGJgG, ddESgGe ai GdJNaja ef hjdGJ GdMQhH, hdMeGjI GdVMGjG GdPjf dG jTGQchf ai GdYedjGJ GdMQHjI, ef GdLQMi hGdeQVi hGdCSQi hGdeOfjjf, HGdEVGaI Edi JhajQ GdMeGjI ddefTBJ GdOjfjI hGdKbGajI hGdCYjGf GdeOfjI, eY GdETGQI dOhQ GdOhdI GdMGejI deQGbHI eOi EdJRGe CWQGa GdfRGY HJWHjb ahGYO GdbGfhf GdOhdi GdEfSGfi(B. (3HjO Cfg YfO MOhK EfgjGQ dGJaGb GdSdGe Hjf CWQGa GdfRGY, JXgQ GdMGLI Edi EjLGO WQa CNQ ddbjGe HGdOhQ GdQbGHi Ydi JfajP GdbGfhf GdOhdi GdEfSGfi, NGUI aj Xd fOQI GddLhA dJaYjd BdjI GdOhdI GdMGejI hBdjGJ GdQbGHI GdCNQi, ef CLd Pdc PgH GdHGMK ddYed Ydi EKHGJ EecGfjI Jcdja YedjGJ MaX GdSdGe GdOhdjI HegGe GdQbGHI hGdETQGa Ydi JfajP bhGYO GdbGfhf GdOhdi GdEfSGfi, deG jJejR Hg ehbYge Hjf CWQGa GdfRGY, hEJSGe Yed CaQGOgG HGdMjGO hGdfRGgI hGdaYGdjI, hPdc ef NdGd GdYOjO ef GdehGKjb hGdEJaGbjGJ GdOhdjI GdYGdejI hGdEbdjejI(B. s
After the outbreak of the Second World War, which left a huge number of victims, violations and crimes against humanity, the United Nations organization was established, as its charter included the desire of states to seek peace, development and cooperation in order to restore international stability and security. The United Nations uses a number of tools to help on finding peaceful solutions to international conflicts, such as preventive diplomacy, peacemaking, and the establishment of peacekeeping operations, based on the deployment of military personnel from the participating countries among the parties to the armed conflict, in addition to participate in capacity building efforts for the national institutes for the operations host countries, through the police and civil components, all of which operates under the international organization flag. The Geneva Conventions (1949) and their protocols were also concluded to contribute to alleviating the scourge of wars, and to protect the wounded, sick, prisoners of wars and civilians who do not participate in the war operations, in addition to provide protection for religious and cultural facilities and civil objects which reference to the role of the protecting state to oversight the extent of the commitment of the parties to the conflict, to implement the rules of International Humanitarian Law. However, when the peace agreement collapses among the parties to the conflict, the need arises to find another party to play the oversight role on the implementation of International Humanitarian Law rules, especially in light of the scarcity of resorting to activating the mechanism of the protecting power and other oversight mechanisms. For this, the researcher went to sought on providing the possibility of entrusting the International Peacekeeping Operations with the tasks of oversight and supervising the implementation of international humanitarian law rules, because of what is distinguished by their location among the parties to the conflict, and the characterization of the work of its personnel with impartiality, integrity and effectiveness through many global and regional international charters and conventions.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdOhdj, (B2022s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B314-356s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3YedjGJ MaX GdSdGes; (3GdQbGHI GdOhdjIs; (3GdbGfhf GdOhdi GdEfSGfis; (3GdeSFhdjI GdOhdjIs; (3efXeI GdCee GdeJMOIs; (3GdefXeGJ GdEbdjejI GdOhdjIs; (3GJaGbjGJ Lfjas; (3GddLfI GdOhdjI ddUdjH GdCMeQ s; (3GdeMceI GdLfGFjI GdOhdjI s; (3GdbGfhf GdOhdj GdEfSGfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs